The Effect of Solvability and Profitability on Audit Delay in Property and Real Estate Companies - Ian Riana; Silviana; Dianti Wulan Suci (International Journal of Social Science and Business, 2023)
The Covid-19 pandemic that occurred in 2020 had a huge impact on various sectors. Low economic growth forecasts and delays have also plagued the domestic real estate market. This study aims to analyze the effect of Solvency and Profitability on Audit Delay in Property and Real Estate Companies for the 2020-2021 period. Solvency ratio is proxied by Debt Equity Ratio (DER) while Profitability is proxied by Return on Assets (ROA). Sample selection using purposive sampling techniques and obtained samples as many as 62 samples of Property and Real Estate Companies. The data in this study is secondary data obtained from the Indonesia Stock Exchange (IDX) and the company's official website. The statistical methods used are descriptive and associative. The data analysis used in this study is regression analysis of panel data with 3 approaches, namely Common Effect, Fixed Effect, and Random Effect Model. Model testing was carried out with 3 model tests namely Chow, Hausman, and Lagrange Multiplier using eViews 12 to determine the effect of profitability and solvency on audit delay. The results showed that the solvency ratio (Debt Equity Ratio) had no effect on audit delay and profitability (Return on Assets) had no effect on audit delay. The finding that solvency ratios and profitability do not affect audit delay has direct implications for the company's financial management policy. These conclusions provide practical guidance for practitioners and decision makers.